ORGANISATIONS HUMANITAIRES FACE A LA LUTTE CONTRE COVID-19. Cas de la Croix-Rouge dans la Ville d’Isiro. - Damas ESOLE KESOLE KAYA (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2021)
The town of Isiro, in the Democratic Republic of Congo, was shaken by the first reported cases of Covid-19 and remained almost indifferent to the controversial existence of this pandemic. The Red Cross appeared at the time to be the only organisation to have carried out a response for the population. The present study allows us to understand the real contribution made by this humanitarian organisation during the "first wave" of Covid-19. Thus, thanks to the functional approach and the underlying data collection and processing tools, it is shown that this contribution was summarised in the sensitisation of community members and the disinfection of certain public premises. However, the contribution of the Red Cross, although salutary, was immediately diluted by the community’s resistance to barrier actions and the lack of material and financial resources. Hence, the need for an effective commitment of all the socio-political and health forces in order to succeed in the fight against this scourge.